Protective Mechanism of Hydrogen Sulfide against Chemotherapy-Induced Cardiotoxicity - Du, Shuxu; Huang, Yaqian; Jin, Hongfang; Wang, Tianyou (Frontiers in Pharmacology, 2018)
Over the past few decades, the number of long term survivors of childhood cancers has been increased exponentially. However, among these survivors, treatment-related toxicity, especially cardiotoxicity, is becoming the essential cause of morbidity and mortality. Thus, preventing the treatment-related adverse effects is important to increase the event free survival during the treatment of cancer in children and adolescents. Accumulating evidence has demonstrated that hydrogen sulfide (H2S) exerts a protective role on cardiomyocytes through a variety of mechanisms. Here, we mainly reviewed the cardioprotective role of H2S in the chemotherapy, and emphatically discussed the possible mechanisms.